PKM Sosialisasi Mitigasi dan Kesiapsiagaan Bencana Alam di SMA N 2 Kota Solok - Tri Gamela Saldy; Riko Maiyudi; Yoszi Mingsi Anaperta; Harizona Aulia Rahman; Rizto Salia Zakri (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract. Natural disasters are disasters caused by the event or series of events due to nature. Natural disasters in recent years are very common and need preparedness, awareness and vigilance in the face of disaster, especially in the city of Solok, starting from earthquakes, landslides and so forth.Yet there is no socialization of natural disasters and disaster preparedness in SMA N 2 kota Solok so that students do not have the knowledge to mitigation and preparedness of natural disasters make the executor to conduct socialization mitigation and natural disaster preparedness to them.So that the participants in this case students understand about how to mitigate and preparedness natural disasters. The socialization is given in the form of lectures, discussions, and field practices.After the socialization was obtained increased knowledge about the mitigation of natural disasters by the students SMAN 2 Kota Solok. At pre-training (prior to training) only 71% of students who understand about mitigation and preparedness and at post-training increased to 100% of students understand the mitigation of natural disasters.Keywords: Disaster management Natural disasters, , mitigation and preparedness